DIE ADMINISTRATIEWE DIENSKORPS - Grobler, J.E.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
The Administrative Service Corps was officially established In 1949.The history of administrative services In the South African Defence Force, however, stretches back to the establishment of the Department of Defence In 1912. An administrative staff for that Department had to be appointed at its Inception. The First World War was responsible for a substantial Increase In administrative duties, but after the end of the German South West Africa campaign considerable reductions followed. During the period between the two World Wars, organisational changes in administrative services took place. Amongst other things, a Service Corps, an Ordnance Corps and an Administrative, Pay and Clerical Corps were established In 1923.At the outbreak of the Second World War in 1939 these three Corps were disbanded and taken over by the newly formed ’Q’ Services Corps, which was renamed Administrative Service Corps in 1949. In the first years after Ita establishment, training of the personnel of the Administrative Service Corps was somewhat neglected. The result was an Impression that the Defence authorities would be satisfied with a low standard of Corps personnel, and a stigma of slackness was thus attached to the Corps. Although the standard of training was drastically raised, especially during the early seventies, the stigma remained right up to the disbandment of the Corps In 197&.That stigma, coupled with the vague Corps organisation which crippled the efficiency of the Corps, was one of the main reasons for the eventual disbandment. The Corps was only two years old when the first of many attempts to disband It was launched. Eight Corps were separated from the Administrative Service Corps before final disbandment, which occurred In 1975. The history of the Administrative Service Corps is a history of the attempts to disband It, and the reasons for the failure of most of those attempts.